Sustainable Pharmaceutical Waste Management Using Quality Methods Function Deployment at PT Bio Farma - Abdurrahman Faris Indriya Himawan; Vania Nanda Fitri (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
Waste management is a critical factor influencing corporate sustainability , particularly in the pharmaceutical industry where production growth parallels rapid population increase . This study aims to evaluate the effectiveness of waste management practices at PT Bio Farma using the Quality Function Deployment (QFD) method . Employing a mixed method approach with a case study design , the research identifying the environmental dimension as the most critical factor , emphasizing corporate commitment to waste management , the efficiency of waste segregation and collection systems , and the availability of recycling facilities . QFD provides a structured framework to translate stakeholders needs into technical responses , offerings strategic recommendations to enhance both operational efficiency and environmental sustainability .